Pagina de inicio
/
Matemáticas
/
Is the inverse a function? h(x)=sqrt [3](x)-4 D yes no Write the inverse function in the form a(bx+c)^3+d , where a, b , c, and d are constants . Simplify any fractions. h^-1(x)=square

Problemas

Is the inverse a function?
h(x)=sqrt [3](x)-4
D yes
no
Write the inverse function in the form
a(bx+c)^3+d , where a, b , c, and d are
constants . Simplify any fractions.
h^-1(x)=square

Is the inverse a function? h(x)=sqrt [3](x)-4 D yes no Write the inverse function in the form a(bx+c)^3+d , where a, b , c, and d are constants . Simplify any fractions. h^-1(x)=square

Solución

avatar
Amandaélite · Tutor durante 8 años
expert verifiedVerificación de expertos
4.1 (239 votos)

Responder

The inverse function is \(h^{-1}(x) = (x + 4)^3\).

Explicar

## Step 1<br />The given function is \(h(x) = \sqrt[3]{x} - 4\). To find the inverse of this function, we first replace \(h(x)\) with \(y\), which gives us \(y = \sqrt[3]{x} - 4\).<br /><br />## Step 2<br />Next, we swap \(x\) and \(y\) to get \(x = \sqrt[3]{y} - 4\).<br /><br />## Step 3<br />Now, we solve for \(y\) to find the inverse function. We start by adding 4 to both sides of the equation to isolate the cube root term on one side. This gives us \(x + 4 = \sqrt[3]{y}\).<br /><br />## Step 4<br />To get rid of the cube root, we cube both sides of the equation, which gives us \((x + 4)^3 = y\).<br /><br />## Step 5<br />Finally, we replace \(y\) with \(h^{-1}(x)\) to get the inverse function. This gives us \(h^{-1}(x) = (x + 4)^3\).
Haz clic para calificar: